Role Of Prosecutor's Laws in Submission of Civil Services Against Submission of Civil Services in Completion of Stories - Dian Wahyuni; Ismansyah Ismansyah; Yussy Adelina Mannas (Wacana Hukum, 2020)
Corruption or commonly referred to as "white collar crime" is a crime that can affect a country's economy. The perpetrators of corruption crimes are usually people who have power. With his authority,the perpetrators of corruption act arbitrarily, causing losses to the Indonesian state. Marwan Effendy stated that "Corruption by various groups is now seen as an extraordinary crime (extrardinary crime), therefore the response can no longer be pursued only by conventional means, but requires extraordinary handling. Corruption starts from the investigation process, prosecution until the court requires high costs, often these costs are not proportional to the value of losses incurred due to corruption. Corruption is an organized crime, this is not possible by a single perpetrator of corruption.